Studi In Silico: Analisis ADME dan Toksisitas Muntingia calabura (Wellness And Healthy Magazine, 2021)
Muntingia calabura is a traditional medicinal plant in Indonesia. Bioactive compounds such as squalene, triglyceride, linoleic acid, a-linolenic acid, B-sitosterol, and stigmasterol contained in these plants show their potential as medicinal plants. This study aims to determine the potential of the bioactive compound Muntingia calabura that can function as a drug using the in silico approach. In this study, pharmacological effects were tested which included absorption, distribution, metabolism, and excretion (ADME) and toxicity (Tox) of the bioactive compound Muntingia calabura. The ADME-Tox effect analysis was carried out using the FAF-Drug4 web application-based method. The bioactive compound a-linolenic acid has the potential as a new drug compound. The bioactive compound a-linolenic acid has a MW: 278.43; LogP: 4.95, 3.4; tPSA: 40.13; HBD: 1; HBA: 2; Solubility: 2342.23 mg/L; Veber rule: Good; Egan rule: Good, 4/400: Good; 3/75: Warning; and has no deviation from Lipinski's five rules. This research requires further in vitro and in vivo test stages as a validation step of the bioactive compound a-linolenic acid Abstrak: Muntingia calabura merupakan tanaman obat tradisional di Indonesia. Senyawa bioaktif seperti squalene, triglyceride, linoleic acid, a-linolenic acid, B-sitosterol, dan stigmasterol yang terdapat pada tanaman tersebut menunjukkan potensinya sebagai tanaman obat. Penelitian ini bertujuan untuk mengetahui potensi senyawa bioaktif Muntingia calabura yang dapat berfungsi sebagai obat dengan metode pendekatan in silico. Pada penelitian ini dilakukan uji efek farmakologi yang meliputi absorpsi, distribusi, metabolisme, dan ekskresi (ADME) dan toksisitas (Tox) senyawa bioaktif Muntingia calabura. Analisis efek ADME-Tox dilakukan dengan metode berbasis aplikasi web FAF-Drug4. Senyawa bioaktif a-linolenic acid berpotensi sebagai senyawa obat baru. Senyawa bioaktif a-linolenic acid memiliki MW: 278,43; LogP: 4,95, 3.4; tPSA: 40,13; HBD: 1; HBA: 2; Solubility: 2342,23 mg/L; Veber rule: Baik; Egan rule: Baik, 4/400: Baik; 3/75: Waspada; dan tidak memiliki penyimpangan dari lima aturan Lipinski. Penelitian ini memerluka tahap uji lanjut in vitro maupun in vivo sebagai langkah validasi dari Senyawa bioaktif a-linolenic acid.